Zoning of green areas circundants to Josefina Teixeira de Azevedo School, in Guanambi-BA - Castro, Jane Mary Lima; Bomfim, Ivanilda Almeida Soares (Geosaberes, 2019)
The predominance of green areas in the urban environment represents an important organizing element of the space through the forestation of squares, parks, gardens, woods and reserves. Environmental zoning is a planning of space occupation in an orderly manner and according to its characteristics and potentialities, functioning as an indicator of environmental quality and quality of life. The present article instigated the students of the 9th grade, from Elementary School II to the research of scientific initiation, with the objective of knowing and zoning the green areas surrounding the school and community and its importance for the aesthetic, functional and environmental quality of the city. The results evidenced that the urban expansion led to an intense process of degradation of the vegetation areas of the urban perimeter of Guanambi, resulting from the disordered urban process without planning and zoning of these areas.